Possible fictions: The testimony of applied performance with women in prisons in England and Brazil - McAvinchey, Caoimhe (2007)
PhDThis thesis is based on a practice based research project with women in prison led by Lois Weaver, Peggy Shaw and myself. The project, Staging Human Rights II, took place in two prisons in England, HMP Highpoint and HMP and YOI Bullwood Hall, and two prisons in Brazil, Presidio Nelson Hungria and Penetenciaria Talavera Bruce. The research was conducted between September 2001 and June 2003. The project was part of a larger, umbrella programme, Staging Human Rights, which sought to find ways, through performance methodologies, in which the language of human rights could incorporate the everyday lives and experiences of people within the criminal justice system. Within this context, Weaver and Shaw called upon non-cognitive, postmodern performance strategies through which the women in prison witnessed their own lives through the testimony of performance. Theoretical considerations of witness and testimony frame the thesis, situating performance as an act of witness, and positioning testimony as an urgent and critical epistemological act in the field of Applied Performance. My research was guided by two questions: what can be known of the possibilities of performance by working with women in prison? What can be known of the context of women's prisons through performance? The thesis is structured into two sections. Section I, made up of Chapters 1-5, considers the theoretical and practical contexts in which the practice based research was undertaken. Section II, Chapter 6, considers each of the five performance residencies and In The House, the performance event in which the research culminated on 23 June 2003. This section calls upon performative writing to both describe and reflect upon the practice and its context. Through writing this thesis, I am bearing witness to what I have come to understand of the possibilities of performance and the experiences of women in prison through performance practice with women in prison